DETERMINAN KONSUMSI PADA NEGARA MAYORITAS BERPENDUDUK MUSLIM DAN NON-MUSLIM: STUDI KASUS INDONESIA DAN SINGAPURA - Muhammad Anif Afandi; Muhammad Amin (Universitas YARSI, 2019)
Consumption is an activity carried out to fulfill the needs of human life. In the principles of conventional economics, the main purpose of consumption activity is to achievemaximum satisfaction. However, the main purpose of consumption activities according to Islamic economics principles is to achieve maslahah. The purpose of this study isto know the factors that affect consumption in a country with majority of moslim and non-moslim populations with sample Indonesia and Singapore. To find out the factors that affectconsumption in those countries, then use secondary data with type of time series in the period 1987 - 2017 which are obtained from the publication of the World Bank. Thedependent variable used is the amount of consumption included goods and services in Indonesia and Singapore, while the independent variables used are macroeconomicvariables consisted by the level of nominal income in Indonesia and Singapore, real interest rate, and average exchange rate of the Rupiah and Dollar Singapore per US Dollar. The method used in this study is Vector Error Correction Model (VECM) with three main outputs namely Granger Causality, Impulse Response Function (IRF), and Variance Decomposition (VDC). The results show that there are three one-way causality relationships in thevariables used for Indonesia and Singapore. In addition, the estimation results of VECM show that the independent variables used have an influence on consumption both in Indonesia and in Singapore. The results of this analysis are also strengthened by the results of consumption responses to shock other variables and the contribution of each independent variables to consumption formation in Indonesia and Singapore.